Effects of KCL on the functional properties of fresh pork sausage - Tolentino, Juvy Paragas; Francisco, Ma. Leonora dL. (2000., 2000)
ABSTRACT The effect of substituting NaCl with KCl at 0, 25, 50, 75 and 100% levels on fresh pork sausage were evaluated in terms of cooking loss, WHC, pH and sensory characteristics. Analysis of Variance and DMRT at 5% level of significance were used to determine differences between treatmeants. Texture and off-flavor were found to be not significantly different among all treatments. Significant differences were found in the overall acceptability, spiciness, saltiness, aroma, longganisa flavor, cooking loss, WCHC and pH. Traces of bitter flavor were present but were found to be weak even at higher levels. The effect of increasing KCl level decreased the overall acceptability and cooking loss of the product but was effective in increasing the pH and WHC. Replacements of up to 50% of the NaCl in fresh pork sausage with KCl were feasible and showed no detrimental effect on the palatability of the product.
Thesis (BSFT)-- University of the Philippines Diliman.
Keywords: Sausages; Potassium chloride